Covid-19 and the restructuring of economic space: Emerging research frontiers in economic geography (with special reference to India) - Singh, Sachinder (National Geographical Journal of India, 2021)
The rst case of COVID-19 was reported in December 2019. However, in no time this local outbreak of the corona virus became a pandemic. Not only it has slowed down the intensity of economic activities across the globe, but it has also resulted in the restructuring of the economic space. Besides, it has also brought in the long term debate on the benets of economic globalization. The article sketches the outlines for the re-examination of the economic space as a consequence of the COVID-19 pandemic. Five research themes are proposed for revisiting economic globalization, workers, inequality, neoliberal economic policies, and development. Studies on these themes will unfold our understanding of the ongoing economic changes from local to global level and we would be in a better position to explain the nature of emerging economic space.